Labour Welfare and Economic Output in Nigeria: An Error Correction Model Analysis of Human Capital Investment, 1990–2024 - Nwankwo, Christopher (Unisia, 2025)
This study investigates how labour welfare influences economic output in Nigeria, aiming to clarify whether investments in workers’ well-being translate into sustained economic growth. Using annual macroeconomic data for 1990–2024, the analysis applies a human capital–based production framework and employs time series techniques, including unit root testing, cointegration analysis, and an error-correction–augmented Ordinary Least Squares model, to examine the long-run and short-run effects of labour welfare, education, health expenditure, government fixed capital formation, and recurrent expenditure on gross domestic product. The results show that labour welfare has a positive and statistically significant impact on economic output in the long run, indicating that better welfare conditions raise productivity and national income, while health expenditure also exerts a significant growth-enhancing effect. By contrast, education spending and recurrent expenditure do not significantly stimulate output, and government fixed capital formation exhibits a surprisingly negative and significant relationship with gross domestic product, suggesting inefficiencies, cost overruns, and abandoned infrastructure projects that fail to contribute to productive capacity. The error correction mechanism reveals a moderate speed of adjustment toward long-run equilibrium, and overall model diagnostics confirm a stable and well-specified relationship between labour welfare and economic output. These findings underscore that strengthening labour welfare, particularly through effective health investment, can be a powerful lever for boosting productivity and inclusive growth, but they also highlight the need to reform public investment management and reorient education and capital spending toward more efficient, growth-supporting uses.